Intercultural marriage in Sarawak : motivational factors. - Juhari, Rumaya; Baharudin, Rozumah; Tan, Jo Pei (University of Malaya, 2008)
Using data gathered from 240 intercultural-married respondents in Sarawak, this study examines motivational factors for intercultural marriage. A 10-item Likert scale adapted from Lewis and Yancey (1997) was used to measure motivational factors to marry inter-culturally. Findings revealed that respondents who earned higher income were not motivated by racial factors such as the uniqueness of intercultural marriage, attractiveness of other races and communication when choosing their partner. Interestingly, those who emphasized on non-racial factors such as love, shared interest, and similar economic status, were also found to consider racial related factors in spouse selection process. To conclude, intercultural-married individuals in the study seemed to be motivated by both racial and non-racial factors to decide upon their marriage.